THE MERDEKA CURRICULUM IN CHARACTER EDUCATION WITH THE EXPLORATION OF A HOLISTIC APPROACH AT POLMAN SCHOOL, MANDAR SULBAR - Rifai, Mesrawati; Mahmud, Natsir; Kasim, Amrah; Muzakkir, Muzakkir; Makduani, Rivai (International Journal of Multidisciplinary Research and Literature, 2024)
A holistic educational approach underscores the significance of comprehensive child development, integrating cognitive, social, emotional, and physical dimensions. Experiential learning through interaction with the environment facilitates optimal growth and development in children. The Merdeka Curriculum for schools introduces the concept of holistic learning, integrating various aspects of child development and creating learning experiences relevant to their lives. Teachers are crucial in creating a safe, comfortable, and loving environment that allows children to feel valued and learn well. Play-based learning in schools strengthens children's motor, cognitive, and social-emotional skills. Implementing a holistic approach in this curriculum necessitates ongoing support for educators through training and coaching to improve their ability to manage child-based learning. Thus, a holistic approach is critical to ensuring optimal and high-quality early childhood development